2018
DOI: 10.1016/j.jped.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Glucose alteration and insulin resistance in asymptomatic obese children and adolescents

Abstract: Notably, this study found a high prevalence of glucose and insulin disorders in asymptomatic obese children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
3
11
0
3
Order By: Relevance
“…Also, Lavrador et al [18] observed that obese patients had higher frequencies of alterations in blood glucose, HOMA-IR, triglycerides and blood pressure. In agreement with our study, Assunção et al [19] reported a high prevalence of glucose metabolism and insulin abnormalities in this population of obese and severe obese children and adolescents, similarly to the findings described by D'Adamo and Caprio [20].…”
Section: Discussionsupporting
confidence: 93%
“…Also, Lavrador et al [18] observed that obese patients had higher frequencies of alterations in blood glucose, HOMA-IR, triglycerides and blood pressure. In agreement with our study, Assunção et al [19] reported a high prevalence of glucose metabolism and insulin abnormalities in this population of obese and severe obese children and adolescents, similarly to the findings described by D'Adamo and Caprio [20].…”
Section: Discussionsupporting
confidence: 93%
“…Insulin resistance and leptin act to reduce food intake and to increase energy expenditure through the action on the hypothalamic neurons, for which they are named “signals of body adiposity” [ 14 ]. Excessive weight contributes to hyperleptinemia, a condition in which the leptin receptors are altered or defective at the blood-brain barrier, resulting in a resistance, and ceasing to regulate body weight and appetite [ 15 , 18 ]. Baseline leptin and insulin concentrations may be positively correlated to insulin-sensitive individuals and both decrease in response to weight loss [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such risk behaviors can induce to overweight, mainly due to the imbalance between high consumption of high-calorie diet and low total daily energy expenditure [ 10 ]. This positive energy balance can directly contribute to the excess of body fat percentage (BF%) and, consequently, to an increase in blood pressure [ 11 , 12 ], triglycerides, free fatty acids [ 13 ], leptin production [ 14 , 15 ], dyslipidemias, hyperuricemia [ 16 , 17 ], and insulin resistance [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of insulin resistance is the adipose tissue excess, responsible for many metabolic effects: increased circulating amounts of free fatty acids that directly interfere with insulin signaling, diminished muscle glucose uptake, increased gluconeogenesis in liver and exaggerated triglyceride synthesis. The adipose tissue further stimulates progression of AN through various adipokines such as: leptin, adiponectin, tumor necrosis factor-α and interleukin-6 (43,44). When the excess insulin needed can no longer be secreted by pancreatic β-cells, type 2 diabetes mellitus occurs.…”
Section: Pathological Conditions and Disorders Associated With Acanthmentioning
confidence: 99%